Aceleração do processo de compostagem de lodos gerados em reatores UASB com inóculo comercial - Boina, Welliton Leandro de Oliveira (2018)
Brazil still faces very serious problems currently related to the management of solid waste in various sectors. Among the most diverse waste generated daily, sewage sludge deserves special mention due to its problematic and often neglected final disposition. The great concern resulting from the inadequate management of this type of waste lies in the fact that it is a contaminant due to the presence of pathogenic microorganisms and toxic metals that are harmful to human health and the environment. However, as an alternative, commonly between treatments and final provisions, what is more evident is the reduction of volume and humidity for disposal in landfills. At present there is no denying certain prerogatives that meet this type of possibility, such as the scarcity of areas suitable for the construction of landfills and the guidelines related to the integrated management and solid waste management governed by Law No. 12,305 / 10, regulated by Decree No. 7.404 / 10, of December 23, 2010, which establishes the National Solid Waste Policy (PNRS). Thus, the biooxidation of sanitary sewage sludge by means of the composting process can improve the physical, chemical and biological qualities of the waste, as well as represent a promising alternative to soil conditioning chemical compounds. In this sense, this study presents results of the composting process of sanitary sewage sludge generated in UASB reactors through the use of commercial inoculum. The objective of this study was to evaluate the efficiency of the commercial inoculum in the composting process. During the composting process, analyzes of temperature, humidity, pH, electrical conductivity and solids contents (total, fixed and volatile) were performed, as well as the agronomic parameters of the organic compounds obtained in the final composting process. In view of the above, the results of the analyzes carried out during the composting process did not show significant improvements that justify the use of the commercial inoculum when compared to the results obtained in the composting process that did not use the commercial inoculum. Likewise, the evaluation of the analyzes performed on the organic compounds obtained at the end of the composting processes (inoculated and conventional), did not present significant changes that justify the use of the commercial inoculum. Thus, in view of the procedures in which the study was developed and considering the type of sanitary sewage sludge and the structural material used, the use of commercial inoculum in the composting process did not provide significant improvements to the point of justifying its use, with the microorganisms being native present in the system sufficient for the degradation process of organic matter.